Incidence of constipation in an intensive care unit - Guerra, Tatiana Lopes de Souza (Associação Brasileira de Medicina intensiva, 2013)
OBJECTIVES: To evaluate the incidence of constipation in critical patients on enteral nutrition in a hospital intensive care unit and to correlate this incidence with the variables found for critical patients. METHODS: The present investigation was a retrospective analytical study conducted in the intensive care unit of Hospital Regional da Asa Norte (DF) via the analysis of medical records of patients admitted during the period from January to December 2011. Data on the incidence of constipation and enteral nutritional support, gastrointestinal changes, stool frequency, ventilatory support, and outcomes were collected and analyzed. RESULTS: The initial sample consisted of 127 patients admitted to the unit during the period from January to December 2011. Eighty-four patients were excluded, and the final sample consisted of 43 patients. The incidence of constipation, defined as no bowel movement during the first 4 days of hospitalization, was 72% (n=31). The patients were divided into a control group and a constipated group. The group of constipated patients reached the caloric target, on average, at 6.5 days, and the control group reached the caloric target in 5.6 days (p=0.51). Constipation was not associated with the length of hospital stay, suspension of nutritional support, or outcome of hospitalization. There was an association between evacuation during hospitalization and a longer duration of hospitalization for a subgroup of patients who did not evacuate during the entire period (p=0.009). CONCLUSION: The incidence of constipation in the unit studied was 72%. Only the absence of evacuation during hospitalization was associated with longer hospital stays. Constipation was not associated with the length of hospital stay, suspension of nutritional support, or outcome of hospitalization.